GRANULOMATOSIS WITH POLYANGIITIS: A 17 YEAR EXPERIENCE FROM A TERTIARY CARE HOSPITAL IN PAKISTAN - Gilani, Jaleed Ahmed; Ashfaq, Muhammad Areeb; Irfan, Omar; Khan, Javaid Ahmed (Journal of Ayub Medical College Abbottabad, 2019)
Granulomatosis with Polyangitis (GPA) is an uncommon immunologically mediated necrotizing vasculitis affecting the small and medium sized systemic blood vessels. We previously reported our experience with this condition and herein, we document our study findings and compare them to the clinical and radiological findings of various studies from around the world. By doing so we hope to further create awareness of this condition afflicting not only our part of the population but is part of a larger global phenomenon. Keywords: Vasculitis; Granulomatous Diseases; Lung